Chimeric Anterolateral Thigh and Rectus Femoris Flaps for Reconstruction of Complex Oral and Maxillofacial Defects. Issue 5 (July 2021) - Li, Panchun; Zhang, Shanshan; Liu, Jiang; Xu, Yuming; Wu, Hanjiang; Gong, Zhaojian
Abstract : Purpose: Complex oral and maxillofacial defects are continuously a challenge for reconstructive surgeons. This study evaluates the effects of chimeric anterolateral thigh (ALT) and rectus femoris flaps for the reconstruction of such defects. Patients and Methods: A retrospective review was performed of 10 patients who underwent reconstruction of oral and maxillofacial defects with chimeric ALT and rectus femoris flaps from October 2014 through August 2016 at the Second Xiangya Hospital. Results: All 10 patients were male, with a mean age of 53.6 years. Postoperatively, all flaps survived completely, without vascular compromise or major wound complications. Salivary fistula occurred in 1 patient, and wound effusion of the thigh occurred in another patient. Gradual wound healing was observed after repeated dressing changes. The patients were followed for approximately 3 to 46 months, the appearance and oral functions were recovered well, and no thigh motor dysfunctions were observed. Conclusions: Because of the convenient flap design, effective avoidance of recipient site complications, lower donor site morbidity, and acceptable functional and esthetic results, chimeric ALT and rectus femoris flaps are a good choice for the reconstruction of complex oral and maxillofacial defects. Abstract : Supplemental Digital Content is available in the text